The Influence of Discipline, Incentives, and Work Motivation on the Performance of Generation Z Employees at Mina Store - Khotimah, Umi; Soejoko, Dodi Kusuma Hadi (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : The purpose was to asses the effect of work discipline, incentives, and work motivation on the performance of generation Z employees at Toko Mina. Design/Methode/Approach : Study uses a quantitative approach. The people study were 30 Toko Mina employees with an age range of 17-25 old who fell into the people Z category at Toko Mina. Research Finding : The case are not fully operatonal  discipline Variable has a notable effect on employee performance., but the incentive and work motivation variables have no significant effect on employee performance. Simultaneously, the variables of work discipline, incentives, and Work motivation substantially impacts the performance of generation Z employees at Toko Mina. Theoretical contribution/Originality : Not many studies have examined the performance of generation Z employees. Practitionel/Policy implication : Can be used for human resource development at Toko Mina Research limitation : This study delay in responses research respondents